Diversity-oriented natural product platform identifies plant constituents targeting Plasmodium falciparum. (December 2016) - Zhang, Jin; Bowling, John; Smithson, David; Clark, Julie; Jacob, Melissa; Khan, Shabana; Tekwani, Babu; Connelly, Michele; Samoylenko, Vladimir; Ibrahim, Mohamed; Zaki, Mohamed; Wang, Mei; et al.
Abstract Background A diverse library of pre-fractionated plant extracts, generated by an automated high-throughput system, was tested using an in vitro anti-malarial screening platform to identify known or new natural products for lead development. The platform identifies hits on the basis of in vitro growth inhibition ofPlasmodium falciparum and counter-screens for cytotoxicity to human foreskin fibroblast or embryonic kidney cell lines. The physical library was supplemented by early-stage collection of analytical data for each fraction to aid rapid identification of the active components within each screening hit. Results A total of 16, 177 fractions from 1300 plants were screened, identifying severalP. falciparum inhibitory fractions from 35 plants. Although individual fractions were screened for bioactivity to ensure adequate signal in the analytical characterizations, fractions containing less than 2.0 mg of dry weight were combined to produce combined fractions (COMBIs). Fractions of active COMBIs had EC50 values of 0.21–50.28 and 0.08–20.04 µg/mL against chloroquine-sensitive and -resistant strains, respectively. InBerberis thunbergii, eight known alkaloids were dereplicated quickly from its COMBIs, but berberine was the most-active constituent againstP. falciparum . The triterpenoidsα -betulinic acid andβ -betulinic acid ofEugenia rigida were also isolated as hits. Validation of the anti-malarial discovery platform was confirmed by these scaled isolations fromB. thunbergii andE. rigida . Conclusions These results demonstrate the value of curating and exploring a library of natural products for small molecule drug discovery. Attention given to the diversity of plant species represented in the library, focus on practical analytical data collection, and the use of counter-screens all facilitate the identification of anti-malarial compounds for lead development or new tools for chemical biology.